Conceptualising European Privatisation Processes After the Great Recession. Issue 3 (21st December 2015) - Mercille, Julien; Murphy, Enda
Abstract: A wave of privatisation is unfolding in Europe in the wake of the financial crisis, but it has yet to receive serious scholarly attention. This paper examines the case of Ireland, where an austerity strategy and European Union International Monetary Fund bailout conditionality have given impetus to the transfer of public assets to the private sector. Theoretically, the paper explains the roots of the phenomenon with reference to a reformulated concept of "accumulation by dispossession" whose usefulness lies in emphasising the politico‐economic drivers of privatisation, which have been neglected in the mainstream literature. A typology is presented that argues that accumulation by dispossession manifests itself, in practice, through four main processes: (1) private repossession of assets nationalised during the financial crisis; (2) restructuring of state‐owned enterprises; (3) commodification of assets and services hitherto located outside the market; and (4) privatised stimulus through public–private partnerships. The paper's framework should be useful to conceptualise ongoing privatisation processes in other European countries.